GSTM1 and GSTT1 Polymorphisms and Susceptibility to Acute Myeloid Leukemia: A Case-control Study of the Sudanese Population - Babekir, Ebtihal Ahmed; Abdelateif, Nour Mahmoud; Adelrahim, Saadia Osman; Hassan, Rosline; Ibrahim, Ibrahim Khider (Asian Pacific Journal of Cancer Biology, 2019)
Background: Glutathione S-transferase (GST) enzyme levels are associated with risk of many types of cancers, including hematological malignancies. In this study we here aimed to investigate the relationship between GSTM1 and GSTT1 polymorphisms and the risk of AML. Conflicts in the published results and the absence of similar in-depth studies in Sudan prompted us to perform the present case-control study to determine the frequency of GSTM1 and GSTT1 polymorphisms in AML patients and their possible association with AML in a Sudanese population. Materials and Methods: A total of 40 patients with AML and 40 control subjects were enrolled in this study. Blood samples were collected from all patients in EDTA containing tubes. Genomic DNA was extracted from all blood samples using salting out method. Genotyping for detection of GSTM1, and GSTT1 polymorphisms was performed for both patients and controls using a multiplex PCR. Results: We reported that there is an association between the GSTM1 null genotype and AML risk (OR= 2.7, 95% CI= 1.2-6.04; P.value = 0.012), the GSTT1 null genotype appeared also to have an influence in the development of AML (OR= 4.93, 95% CI= 1.6-15.07; P.value = 0.005). Conclusion: These findings indicate that genetic variants of GSTM1 and GSTT1 genes may increase individual susceptibility to AML.